PENELITIAN MODEL PEMBELAJARAN PJBL DAN PBL DI SEKOLAH DASAR : SYSTEMATIC LITERATURE REVIEW - Muhammad Syarif Hidayatulloh; Jihan Rafiadilla; M. Zainal Arifin; Didit Ardianto (STKIP Subang, 2024)
Curriculum implementation in educational units is adapted to 21st century skills, namely increasing collaboration, communication, critical thinking, creativity and computation. PJBL and PBL learning models can foster students' critical thinking skills and improve student learning outcomes. This scientific article was prepared using the Systematic Literature Review (SLR) method. Literature study data was collected using the Publish or Perish (PoP) application and carried out using the keywords